The Cardiac Rehabilitation Psychodynamic Group Intervention (CR-PGI): An Explorative Study - Venuleo, Claudia; Mangeli, Gianna; Mossi, Piergiorgio; Amico, Antonio F.; Cozzolino, Mauro; Distante, Alessandro; Ignone, Gianfranco; Savarese, Giulia; Salvatore, Sergio (Frontiers in Psychology, 2018)
Objective: An explorative study focusing on the process of a Cardiac Rehabilitation Psychodynamic Group Intervention (CR-PGI) addressed to Myocardial Infarction (MI) patients is discussed. The study aimed at analysing whether the treatment based on CR-PGI serves as a communicational context within which MI patients are enabled to explore new interpretations of their post-infarction condition . Method: The intervention, divided into 12 weekly one-hour group sessions, was addressed to MI patients recruited within a Public Hospital of southern Italy. Each session was audio-recorded and Lexical Correspondences Analysis (LCA) was applied to the verbatim transcripts, in order to provide a map of the evolution of the communication exchange occurring over the 12 sessions. Results: The findings showed that the discourses associated to the first eight sessions differed from the discourses of the last four sessions. Two main transitions occurred. The first concerns the response to the infarction, first interpreted as a process of affective elaboration and afterwards as practical management of the functional aspects associated with the condition of M.I. patients. The second concerns the nature of the change and contrasts a lifestyle-oriented model with a social role approach, which refers to social, legal and medical practices related to the acknowledgement of being an M.I. patient. Conclusions: The findings offer preliminary support to the capacity of CR-PGI to work as a context where new meanings for the biographical rupture of the myocardial infarction can be explored. Consistently with the rationale of the model, the intervention seems to have promoted the emergence of new ways of feeling and understanding one’s condition.